2021
DOI: 10.1097/ta.0000000000003251
|View full text |Cite
|
Sign up to set email alerts
|

Dose-dependent association between blood transfusion and nosocomial infections in trauma patients: A secondary analysis of patients from the PAMPer trial

Abstract: BACKGROUND:The Prehospital Air Medical Plasma (PAMPer) trial demonstrated a survival benefit to trauma patients who received thawed plasma as part of early resuscitation. The objective of our study was to examine the association between blood transfusion and nosocomial infections among trauma patients who participated in the PAMPer trial. We hypothesized that transfusion of blood products will be associated with the development of nosocomial infections in a dose-dependent fashion. METHODS:We performed a second… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 23 publications
(59 reference statements)
0
8
0
Order By: Relevance
“…33 In addition to mortality, morbidity occurs quite frequently in the MT population with estimates ranging from 14% to 42%. 34,35 Even after hemorrhage is controlled, the cellular response of individual organ systems and the balance of inflammatory mediators over hours or days can lead to multiple organ failure weeks after the initial insult. 34 As such, it is not surprising that morbidity was selected as a noncore but important outcome.…”
Section: Discussionmentioning
confidence: 99%
“…33 In addition to mortality, morbidity occurs quite frequently in the MT population with estimates ranging from 14% to 42%. 34,35 Even after hemorrhage is controlled, the cellular response of individual organ systems and the balance of inflammatory mediators over hours or days can lead to multiple organ failure weeks after the initial insult. 34 As such, it is not surprising that morbidity was selected as a noncore but important outcome.…”
Section: Discussionmentioning
confidence: 99%
“…To understand the inflammatory response of trauma and the immune consequences of related therapies, future studies should focus on the immunological effects of trauma and transfusion after pediatric injury. Blood product transfusion is a potentially lifesaving therapy for hemorrhagic shock but can be associated with nosocomial infections and mortality in critically ill children and adults 32–35 . The future direction of this research may involve consideration of developing immunomodulating blood products or better characterization of the immunologic patient phenotype.…”
Section: Resultsmentioning
confidence: 99%
“…Blood product transfusion is a potentially lifesaving therapy for hemorrhagic shock but can be associated with nosocomial infections and mortality in critically ill children and adults. [32][33][34][35] The future direction of this research may involve consideration of developing immunomodulating blood products or better characterization of the immunologic patient phenotype. This may include determining which therapies are more advantageous than others based on their immunogenic properties.…”
Section: Researchmentioning
confidence: 99%
“…The PAMPer trial identified a significant reduction in mortality when prehospital FFP was given to trauma patients during air transport [12]. A recent secondary analysis of the trial data evaluated the risk of nosocomial infections with blood transfusions and found that both PRBC and cryoprecipitate transfusion were significantly associated with increased odds of infection [13 â–Ş ]. A dose-dependent relationship between the number of PRBC's transfused and nosocomial infection was identified [13 â–Ş ].…”
Section: Balanced Transfusionmentioning
confidence: 99%
“…A recent secondary analysis of the trial data evaluated the risk of nosocomial infections with blood transfusions and found that both PRBC and cryoprecipitate transfusion were significantly associated with increased odds of infection [13 â–Ş ]. A dose-dependent relationship between the number of PRBC's transfused and nosocomial infection was identified [13 â–Ş ]. Though causality was not established, the relationship suggests benefit to minimizing transfused products, which is aided by a balanced transfusion strategy.…”
Section: Balanced Transfusionmentioning
confidence: 99%